ĪTHĀR CONCEPT OF IBNU QAYYIM AL-JAWZIYYAH’S THIKING AS AN APPROACH TO AVOIDING PEOPLE-PLEASING BEHAVIOR - Dly, Dwi Revalina; Azwar, Alfi Julizun; Ilyas, Deddy (Sekolah Tinggi Agama Islam Sadra, 2025)
This study aims to analyze the concept of īthār in the thoughts of Ibn Qayyim al-Jawziyyah as an approach to avoid people-pleasing behavior. People-pleasing is an individual's tendency to always please others at the expense of personal interests, which can hurt mental health and emotional balance. As an alternative, the concept of īthār, which means prioritizing the interests of others based on sincerity and honesty, offers a healthier solution and is based on Islamic spiritual values. This study uses the theory of Sufism and social psychology to understand the fundamental differences between īthār and people-pleasing. The method used in this study is a qualitative approach with a literature study of the works of Ibn Qayyim al-Jawziyyah, especially Madārij al-Sālikīn and Maḥabbatullah. The study results indicate that īthār is not just a social act, but also part of worship that reflects a balance between personal interests and concern for others without causing psychological stress. In contrast to people-pleasing, which tends to be driven by fear of rejection and the need for social validation, īthār is based on seeking Allah's pleasure and the common good. This study concludes that īthār can be an effective approach to avoid the negative impacts of people-pleasing and help someone build healthier social interactions and improve spiritual quality. The recommendation of this study is the need for a broader understanding of the concept of īthār in character education and psychological guidance, so that individuals can develop a balance between caring for others and maintaining their well-being without getting caught up in people-pleasing attitudes.